KIR/KIR-ligand genotypes and clinical outcomes following chemoimmunotherapy in patients with relapsed or refractory neuroblastoma: a report from the Children's Oncology Group. Issue 2 (23rd February 2023) - Erbe, Amy K; Diccianni, Mitch B; Mody, Rajen; Naranjo, Arlene; Zhang, Fan F; Birstler, Jen; Kim, KyungMann; Feils, Arika S; Hung, Jung-Tung; London, Wendy B; Shulkin, Barry L; Mathew, Varsha; et al.
Abstract : Background: In the Children's Oncology Group ANBL1221 phase 2 trial for patients with first relapse/first declaration of refractory high-risk neuroblastoma, irinotecan and temozolomide (I/T) combined with either temsirolimus (TEMS) or immunotherapy (the anti-GD2 antibody dinutuximab (DIN) and granulocyte macrophage colony stimulating factory (GM-CSF)) was administered. The response rate among patients treated with I/T/DIN/GM-CSF in the initial cohort (n=17) was 53%; additional patients were enrolled to permit further evaluation of this chemoimmunotherapy regimen. Potential associations between immune-related biomarkers and clinical outcomes including response and survival were evaluated. Methods: Patients were evaluated for specific immunogenotypes that influence natural killer (NK) cell activity, including killer immunoglobulin-like receptors (KIRs) and their ligands, Fc gamma receptors, and NCR3. Total white cells and leucocyte subsets were assessed via complete blood counts, and flow cytometry of peripheral blood mononuclear cells was performed to assess the potential association between immune cell subpopulations and surface marker expression and clinical outcomes. Appropriate statistical tests of association were performed. The Bonferroni correction for multiple comparisons was performed where indicated. Results: Of the immunogenotypes assessed, the presence or absence of certain KIR and their ligands was associated with clinical outcomes in patients treated with chemoimmunotherapy rather than I/T/TEMS. While median values of CD161, CD56, and KIR differed in responders and non-responders, statistical significance was not maintained in logistic regression models. White cell and neutrophil counts were associated with differences in survival outcomes, however, increases in risk of event in patients assigned to chemoimmunotherapy were not clinically significant. Conclusions: These findings are consistent with those of prior studies showing that KIR/KIR-ligand genotypes are associated with clinical outcomes following anti-GD2 immunotherapy in children with neuroblastoma. The current study confirms the importance of KIR/KIR-ligand genotype in the context of I/T/DIN/GM-CSF chemoimmunotherapy administered to patients with relapsed or refractory disease in a clinical trial. These results are important because this regimen is now widely used for treatment of patients at time of first relapse/first declaration of refractory disease. Efforts to assess the role of NK cells and genes that influence their function in response to immunotherapy are ongoing. Trial registration number: NCT01767194 .